DAMPAK DUAL BANKING SISTEM PADA STABILITAS PERBANKAN DI INDONESIA - Shimah Fauziah Yeubun; Jukri Baharuddin (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2021)
This study aims to discuss the implementation of the dual banking system at the level of banking stability in Indonesia in terms of the framework and the impact it has. The analysis method uses library research to collect reading references related to the dual banking system and banking stability. The results of the study indicate that the application of the dual banking system is following the diverse characteristics of the Indonesian people and the majority are Muslim. As for banking stability with the implementation of this dual banking system, it has a good impact which provides good justification for countries implementing the process due to several benefits including increasing overall banking stability which is good for the economy; can meet the needs of consumers who want products according to their religious beliefs without sacrificing stability; In times of crisis, Islamic banks are better than conventional so they are relatively immune to crises.